Quality Parameters of Instant Dried Thai Fermented Fish Dip as Affected by Levels of Guar Gum - Duangsai, Pongdanai; Srisataporn, Arunepong; Hauisan, Kannika; Gawborisut, Samsamorn (วารสารแก่นเกษตร, 2019)
Thai fermented fish dip (TFFD), an authentic chili dip commonly consumed in Thailand and Loa People’s Democratic Republic, can be dried and ground into instant dried TFFD. This product can be rehydrated by adding an appropriate amount of hot water, to return it to the original paste-like form. However, it was found that solid particles in rehydrated TFFD deposited at the bottom of the container and separated from the liquid. Using guar gum as a binding agent may reduce this problem. The objective of this experiment was to investigate the effect of various guar gum levels (0, 0.10, 0.20, 0.30, and 0.40%) on the quality parameters of instant dried TFFD power and rehydrated TFFD. Total plate count, yeast and mold count, aw, and CIE color values (L*, a*, and b*) of instant dried TFFD powder were then measured. Texture profile analysis (firmness, consistency, cohesiveness and viscosity), CIE color values (L*, a* and b*), and sensory acceptability of the rehydrated TFFD were also evaluated. The study showed the quality parameters were not affected by the level of guar gum, except b* color parameter of instant dried TFFD powder and the cohesiveness of rehydrated TFFD. The b* parameter was increased as the guar gum level increased. The cohesiveness of the product wassignificantly increased in the samples supplemented with 0.20% guar gum. Thus, 0.20% guar gum is considered the most suitable for TFFD.